Instruments of energy subsidy reforms in Arab countries: The case of the Gulf Cooperation Council (GCC) countries - Mohammad Al-Saidi (Energy Reports, 2020)
Energy subsidies can account for a large share of government expenditures in some GCC countries. In light of fiscal imbalances since 2014, these countries have reiterated their intention to decrease subsidies and substitute them with more targeted support systems. This paper briefly outlines the extent of energy subsidies. The scope and the drivers of the subsidy reform agenda are outlined, citing recent literature. Some instruments are explained such as adjustment of electricity or water tariffs, increasing of fuel prices, and compensation of citizens through cash transfers. However, the adopted reforms are not yet comprehensive and do not alter the social contract of rentier states.
Keywords: 330; Arab countries; Energy efficiency; Energy sector reforms; Energy subsidies; Gulf Cooperation Council; Utility tariffs